Factors Related to the Event Stunting in Toddlers 25-59 Months in the Region Kolongan District Puskesmas North Minahasa District - Atik Purwandari; Gusti Ayu Tirtawati; Sandra Tombokan; Sjeny Tuju; Joice Silangen (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Stunting (short) is a condition of failure to thrive in children under five as a result of chronic malnutrition so that children do not reach the ideal body size for their age. Children who are classified as short (stunting) have experienced chronic malnutrition since the beginning of their lives, on this basis, research on the problem of stunting is important to do. This research is an analytic observational research study with a case control design. The independent variables include age at first pregnancy, maternal height, birth weight, birth spacing, sanitation and clean water, parenting, maternal education, exclusive breastfeeding, complementary feeding and infectious diseases and the dependent variable is stunting. The sample is toddlers aged 25-59 months who experience stunting as many as 33 people. The results showed that there was no relationship between gestational age and stunting, p = 0.609, there was a significant relationship between maternal height and stunting, p = 0.037, there was a significant relationship between birth weight and stunting, p = 0.017, there was no relationship between birth spacing and stunting, p = 0.805, there is no relationship between sanitation and clean water with stunting, p = 0.159, there is no relationship between parenting and stunting, p = 0.802, there is a significant relationship between maternal education and stunting, p = 0.044, there is a significant relationship between exclusive breastfeeding and stunting , p = 0.024, there is a significant relationship between MP ASI and stunting, p = 0.007, there is a significant relationship between infectious diseases and stunting, p = 0.007. Based on the results of this study, many factors influence the incidence of stunting in children aged 25-59 months. For this reason, it is hoped that the Kolongan Health Center, Kalawat District, can improve the performance of midwives and nutrition workers at the puskesmas to be more active in providing counseling and counseling to pregnant women and mothers of children under five for the prevention and control of stunting in the Kolongan Health Center area.